EFL Teachers' Apprehension and L2 Students' Classroom Engagement - Li, Xiaodong (Frontiers in Psychology, 2021)
Teachers’ apprehension is an indispensable part of the educational context since it impacts the amount to which students are engaged in class activities. Although several studies have been carried out considering the role of students’ stress in their engagement, it seems extremely vital to conduct such studies among teachers to measure the link between these two variables. In this study, the author has made endeavors to define one of the apprehension’s categories named communication apprehension and the antecedents of teachers’ apprehension. Then classroom engagement is discussed. Following that, the relevance between the two variables of this research is discussed. Finally, both implications and suggestions for further studies are dealt with.